The effect of creatine supplementation on muscle fatigue and physiological indices following intermittent swimming bouts - Dabidi Roshan, V.; Babaei, H.; Hosseinzadeh, M.; Arendt-Nielsen, L. (The Journal of Sports Medicine and Physical Fitness, 2013)
We evaluated the effect of Creatine (Cr) supplementation on muscle fatigue and physiological indices after intermittent swimming bouts in trained swimmers. Sixteen healthy non-elite swimmers (19±4 years, 75±12 kg) were randomly assigned into two groups of either Cr supplementation or placebo and performed six repeated sprints swimming bouts of 50-m departing every 120 seconds. The Cr group was supplemented 4 times a day for 6 days. Blood lactate, Creatine Kinase (CK), creatinine, heart rate, best repeated sprint (RSb) and mean repeated sprint (RSm) times, and percentage of speed decrement (%Dec) were measured at the various phases of swimming bouts. Repeated measure ANOVA and independent t-student tests showed CK and blood lactate concentration increased gradually after the third and sixth swimming bouts. % Dec in Cr group was significantly lower after 3rd swimming bout, also heart rate in Cr group was associated with lower increase in HR mean (P<0.05) compared to placebo. These results suggest that Cr supplementation may improve swimming performance and reduce increased blood lactate levels following intermittent sprint swimming bouts. In conclusion Cr supplementation in trained swimmers may improve anaerobic performance and heart rate variations independent of the effect of intensive sprint swimming bouts.